Culture Codes Democracy - Ars Electronica Center Linz (Hatje Cantz Verlag GmbH, 2026)
Art as a compass for democracy in times of technological change Culture Codes Democracy is a timely publication exploring how art and cultural critique can help societies rethink their relationship to new technologies. Drawing on the expertise of leading European cultural institutions, it highlights the role of artistic practice in shaping democratic futures. The book distinguishes itself through: - Three thematic sections—Mediated Realities, Speculative Governance, and Hybrid Entities—each showing how art engages with technology and democracy - Contributions from pioneering cultural organisations, offering real-world case studies and insights - A forward-looking perspective, envisioning how art can guide Europe towards digital sovereignty Richly illustrated and thought-provoking, this critical reader is essential for anyone interested in the intersection of art, politics, and technology in shaping tomorrow's democracy.